Core concepts: views from physiology and neuroscience - Schaefer, Jennifer E.; Michael, Joel (Frontiers in Education, 2024)
Core concepts are "big ideas" that are central to a discipline, provide frameworks of understanding for disciplinary content, and aid student transfer of learning. Core concept lists have been developed for increasing numbers of higher education STEM disciplines. This mini-review uses physiology and neuroscience core concepts as examples to inform core concept pedagogies in these and other disciplines. The article reviews the development of physiology and neuroscience core concepts and compares the resulting concept lists. It then provides suggestions or "lessons learned" for educators and researchers who wish to utilize core concept pedagogies or who wish to develop core concepts for other STEM disciplines.